Transaction Cost of Black Market in the Region Timor-Leste Border - Kamilaus Konstanse Oki; Natalia Lily Balubu (Universitas Negeri Malang, 2021)
Timor-Leste’s cross-border trade involves the people of the two countries on the border. Cross-border trade, which was originally facilitated by the government of Indonesia and East Timor by providing a common border market, has been closed since the Covid-19 pandemic. As a consequence, illegal transaction activities continue around the border with an unconventional approach and run outside the control of the state. The study aims to determine the effect of transaction costs, institutional changes, black markets on the welfare of people in border areas directly or indirectly. Explanatory research is a method approach used with PLS (Partial Least Square). The results of the study show that the direct relationship between constructs is positive, except that the transaction cost on welfare is negative. The indirect effect of transaction costs and institutional changes on welfare through the black market is positive. The factor of low transaction costs and changes in people’s behavior and income causes the trading process to be outside the government’s permit. Another supporting factor is the ease of accessibility in the form of proximity to mileage, means of transportation, and the similarity of economic needs. Black market practice is unlawful, and the state loses revenue. Keywords: Transaction Cost, Institutional Change, Black Market, WelfareJEL Classification: D60, F10